2015
DOI: 10.3346/jkms.2015.30.2.207
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Anesthesia-related Medical Disputes in the 2009-2014 Period Using the Korean Society of Anesthesiologists Database

Abstract: Using the Korean Society of Anesthesiologists database of anesthesia-related medical disputes (July 2009-June 2014), causative mechanisms and injury patterns were analyzed. In total, 105 cases were analyzed. Most patients were aged < 60 yr (82.9%) and were classified as American Society of Anesthesiologists physical status ≤ II (90.5%). In 42.9% of all cases, the injuries were determined to be 'avoidable' if the appropriate standard of care had been applied. Sedation was the sec most common type of anesthesia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 26 publications
1
34
0
Order By: Relevance
“…, benzodiazepines and/or opioids), propofol can easily lead to deep sedation or even general anesthesia requiring cardiopulmonary support. A series of reports by the Korean Society of Anesthesiologists (KSA) found that the number of disputed medical cases involving propofol sedation has increased in recent years, and the magnitude of injuries associated with propofol sedation is similar to those with general anesthesia [12]. Significant variation in propofol sedation practices was also found across different types of procedures, clinical specialties, and hospital classes.…”
Section: Introductionmentioning
confidence: 99%
“…, benzodiazepines and/or opioids), propofol can easily lead to deep sedation or even general anesthesia requiring cardiopulmonary support. A series of reports by the Korean Society of Anesthesiologists (KSA) found that the number of disputed medical cases involving propofol sedation has increased in recent years, and the magnitude of injuries associated with propofol sedation is similar to those with general anesthesia [12]. Significant variation in propofol sedation practices was also found across different types of procedures, clinical specialties, and hospital classes.…”
Section: Introductionmentioning
confidence: 99%
“…Our results regarding sedation-related problems are consistent with those of previous studies [13][14][15] showing that respiratory system events were the most common adverse events. Several studies 4,[13][14][15][16][17] have warned of the risk of respiratory depression associated with propofol overdose. The risk of propofol overdose is emphasized because the metabolic ability varies 19-fold among individuals; 18) thus, a lack of sufficient physician attention is related to a high risk of overdose.…”
Section: Discussionmentioning
confidence: 99%
“…The appropriateness of anesthesia was assessed by a reviewer who provided an expert consultation about the assigned cases using a numeric rating scale (NRS) from 1 to 9, in which 1 was the least appropriate and 9 was most appropriate in the process of anesthesia. On the basis of appropriateness, we estimated the preventability of the adverse event or outcome, 4) which was the possibility that a certain injury could have been prevented by appropriate treatment or precautions. NRS 1-3 included preventable events, that is, events that could easily have been prevented; NRS 4-6 included moderately preventable events, that is, events that might have been preventable; and NRS 7-9 included hardly preventable events, that is, events that were unlikely to have been prevented.…”
Section: Outcome Assessmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…This result is attributed to frequent media coverage. In addition, 30 cases of deaths related to sedation made legal disputes in Korea between 2009 and 2014 12. Since ordinary workers also perceives adverse events to be occurring more often as compared to doctors, in order to lower the fear of adverse events a person receiving sedation could feel, there is a need for more detailed explanation about sedation.…”
Section: Discussionmentioning
confidence: 99%